PENGEMBANGAN PERANGKAT LUNAK UNTUK PENGOPERASIAN WADUK WONOGIRI PERIODE BANJIR - , IDHAM RIYANDO MOE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The floods of Solo had caused a lot of losses lately. Therefore, function of flood control is an important consideration as a flood mitigation efforts in the territory of the upstream of Bengawan Solo River Basin, which includes the city of Surakarta, Karanganyar, and Sragen. In order to flood control can operate with very good, one way is through an integrated system for the operation opening gate of spillway at Wonogiri Reservoir. Lack of hydrological information on the flood period, causes uncertainty operation of spillway at Wonogiri Reservoir. So that the software to integrate hydrological information in the catchment area at Wonogiri Reservoir and opening gate of spillway need to be made to improve the performance of flood control more integrated and better. Main procedure that created in this software are three simulation. There are consist of simulation of flood forecasting in catchment area at Wonogiri Reservoir based on the current land use, simulation of flood routing to obtain opening gate of spillway at Wonogiri Reservoir in flood period and the recommendation in rule of opening gate of spillway. Simulation of flood forecasting obtained based on hydrological information from 14 rainfall stasion and base flow from 8 watershed. After that the information will be used to get hydrograph flood inflow in each watershed, and the all of information summed to obtain the total of flood hydrograph who will enter the Wonogiri Reservoir. The next step is simulation of flood routing to obtain opening gate of spillway at Wonogiri Reservoir where the user can determine the maximum outflow adjust bankfull capacity with discharge 400 m 3 /s, of course by looking at the dam safety criteria is maximum elevation +139.1 meter as critical elevation in flood period. The last is the recommendation in rule opening gate of spillway from flood routing simulation. Result of software development with compiler PHP an MySQL showed real-time hydrological information each rainfall station, base flow each watershed, initial elevation of Wonogiri Reservoir and initial opening gate of spillway that received by software can be directly calculated to be total flood hydrograph inflow and can be directly know the operation opening gate of spillway in every single hour. Accuracy of water balanced calculations on this model is less than 1%. This performance indicates that the simulation of flood routing is accurate enough. Thus the model can be applied to improve the performance of flood control at the upstream of Bengawan Solo River Basin.